Prophylaxis of hepatitis B after liver transplantation using low-dose short-course hepatitis B immunoglobulin plus antiviral drug - S. Limsrichamrern (2020)
© JOURNAL OF THE MEDICAL ASSOCIATION OF THAILAND 2019. Background: The most common indication for liver transplantation (LT) in South East Asia is hepatitis B virus (HBV)-related liver disease. Without proper prophylaxis, HBV will recur rapidly after LT. Currently, there is no universally accepted regimen, and most transplant centers use high-dose hepatitis B immunoglobulin (HBIG) for prophylaxis, which is costly. Objective: To review the authors’ experience with low-dose short-course HBIG plus antiviral for HBV prophylaxis. Materials and Methods: Between July 2002 and December 2013, 90 patients who were positive for HBV surface antigen (HBsAg) underwent LT at the authors’ institute. The protocol included continuing previously prescribed antiviral drug or giving lamivudine 150 mg orally before the operation in patients who had never received antiviral drug. All patients received 1,200 to 2,000 international units (IU) of HBIG intravenously during anhepatic phase, and 1,200 to 1,600 IU of intravenous HBIG daily for six days postoperatively. Oral antiviral drug was continued postoperatively. HBV recurrence was defined as the reappearance of HBsAg in serum. Cumulative incidence function was used to calculated cumulative recurrence rate. Results: At the end of follow-up, the post-transplant HBsAg status was positive in six patients (6.7%); two patients at three months, one patient at one year, two patients at seven years, and one patient at ten years after LT. Cumulative HBV recurrence rate was 2.3% at one year, 3.5% at five years, and 11.3% at ten years after LT. The median time-to-recurrence was 49.5 months. All treatments were well tolerated with no serious adverse event. Conclusion: Combination of low-dose short-course HBIG and long-term oral antiviral drug is effective in preventing HBV recurrence after LT. Since HBIG is very expensive, this low-dose short-course HBIG prophylaxis regimen can reduce the cost of LT without increasing the HBV recurrence rate.